Low Frequency Electroacupuncture Alleviated Spinal Nerve Ligation Induced Mechanical Allodynia by Inhibiting TRPV1 Upregulation in Ipsilateral Undamaged Dorsal Root Ganglia in Rats - Yong-Liang Jiang (Evidence-Based Complementary and Alternative Medicine, 2013)
Neuropathic pain is an intractable problem in clinical practice. Accumulating evidence shows that electroacupuncture (EA) with low frequency can effectively relieve neuropathic pain. Transient receptor potential vanilloid type 1 (TRPV1) plays a key role in neuropathic pain. The study aimed to investigate whether neuropathic pain relieved by EA administration correlates with TRPV1 inhibition. Neuropathic pain was induced by right L5 spinal nerve ligation (SNL) in rats. 2 Hz EA stimulation was administered. SNL induced mechanical allodynia in ipsilateral hind paw. SNL caused a significant reduction of TRPV1 expression in ipsilateral L5 dorsal root ganglia (DRG), but a significant up-regulation in ipsilateral L4 and L6 DRGs. Calcitonin gene-related peptide (CGRP) change was consistent with that of TRPV1. EA alleviated mechanical allodynia, and inhibited TRPV1 and CGRP overexpressions in ipsilateral L4 and L6 DRGs. SNL did not decrease pain threshold of contralateral hind paw, and TRPV1 expression was not changed in contralateral L5 DRG. 0.001, 0.01 mg/kg TRPV1 agonist 6′-IRTX fully blocked EA analgesia in ipsilateral hind paw. 0.01 mg/kg 6′-IRTX also significantly decreased pain threshold of contralateral paw. These results indicated that inhibition of TRPV1 up-regulation in ipsilateral adjacent undamaged DRGs contributed to low frequency EA analgesia for mechanical allodynia induced by spinal nerve ligation.